2015
DOI: 10.1002/pits.21892
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Undefinable: Operationalization of Methods to Identify Specific Learning Disabilities Among Practicing School Psychologists

Abstract: Accurate and consistent identification of students with specific learning disabilities (SLDs) is crucial; however, state and district guidelines regarding identification methods lack operationalization and are inconsistent throughout the United States. In the current study, the authors surveyed 471 school psychologists about school SLD identification guidelines and the identification methods actually used (e.g., ability-achievement discrepancy, response-to-intervention, and the evaluation of students' pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 12 publications
(24 reference statements)
4
48
0
Order By: Relevance
“…Thus, school psychologists may be using RtI more frequently and ability–achievement discrepancy less frequently to identify students with SLD. However, it is difficult to directly compare the findings in the current study with the Cottrell and Barrett () findings because the questions regarding SLD identification practices were asked differently in the two studies (i.e., scale of use frequency [Cottrell & Barrett, ] vs. forced choice of primary SLD identification method [This study]).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, school psychologists may be using RtI more frequently and ability–achievement discrepancy less frequently to identify students with SLD. However, it is difficult to directly compare the findings in the current study with the Cottrell and Barrett () findings because the questions regarding SLD identification practices were asked differently in the two studies (i.e., scale of use frequency [Cottrell & Barrett, ] vs. forced choice of primary SLD identification method [This study]).…”
Section: Discussionmentioning
confidence: 99%
“…In short, the Ab‐Ach discrepancy model analyzes the discrepancy between scores on cognitive and achievement assessments, using various statistical methods (Cottrell & Barrett, ; Kavale, ; Reschly & Hosp, ). RtI measures discrepancies in both a student's lower level of performance and lower rate of learning despite the implementation of evidence‐based interventions (Cottrell & Barrett, ; Reschly, ). PSW assesses profiles of strengths and weaknesses in cognitive ability linked to low achievement in an academic domain (Cottrell & Barrett, ; Stuebing, Fletcher, Branum‐Martin, & Francis, ).…”
mentioning
confidence: 99%
“…RtI measures discrepancies in both a student's lower level of performance and lower rate of learning despite the implementation of evidence‐based interventions (Cottrell & Barrett, ; Reschly, ). PSW assesses profiles of strengths and weaknesses in cognitive ability linked to low achievement in an academic domain (Cottrell & Barrett, ; Stuebing, Fletcher, Branum‐Martin, & Francis, ). States, districts, and schools have abandoned the use of Ab‐Ach discrepancy methods and implemented RtI and PSW methods to varying degrees (Barrett, Cottrell, Newman, Pierce, & Anderson, ; Zirkel & Thomas, ).…”
mentioning
confidence: 99%
“…Previous research using these data indicated a large number of participants did not know the operationalization of each of the methods of SLD identification. This may be particularly true for RtI methods as RtI has been described several ways in the literature (e.g., Case et al 2003;Cottrell and Barrett 2015;Fuchs et al 2003;Vaughn and Fuchs 2003;Walker and Shinn 2010) and ethical, legal, and practical considerations for using RtI to identify SLDs have been noted (Burns et al 2007;Reynolds and Shaywitz 2009). These challenges and ambiguity might explain why those working in schools where RtI is required for SLD identification experience lower levels of assessment job satisfaction compared to those working in schools where Ab-Ach is required.…”
Section: Discussionmentioning
confidence: 96%
“…These data were gathered as part of a larger study on SLD identification methods (see Cottrell and Barrett 2015). The study received approval from the Utah State University Institutional Review Board (IRB) in fall 2013.…”
Section: Methodsmentioning
confidence: 99%